Design, modeling and simulation of the control of a 4 DOF exoskeleton - Pena-Chavez, Jhorkaef (2024)
This study presents the design, modeling, and simulation of a 4 DOF (degrees of freedom) exoskeleton aimed at augmenting human mobility and strength, with applications in both rehabilitation and human performance enhancement. By leveraging advanced computational tools and simulation techniques, the research addresses critical aspects of exoskeleton development, including mechanical design, actuation mechanisms, and control strategies. Preliminary mechanical testing of a 3D printed model validates the theoretical design, highlighting the potential of the proposed system to meet the intended performance objectives with a focus on user comfort and safety. The results from simulation studies reveal the precision and adaptability of the control system, demonstrating its capability to execute complex movements with minimal error and respond effectively to dynamic disturbances. Energy efficiency analysis indicates that the chosen actuation methods optimize power consumption, suggesting the possibility of extended operational durations. Although the absence of a fully functional prototype limits the scope of empirical validation, the findings provide a solid foundation for future development. Recommendations include the fabrication and testing of a complete prototype, exploration of usercentric design adaptations, and the integration of advanced control algorithms. This research contributes to the body of knowledge in exoskeleton technology, offering insights that could accelerate the development of accessible and effective mobility.